1992
DOI: 10.1073/pnas.89.1.348
|View full text |Cite
|
Sign up to set email alerts
|

An ancient clonal lineage in the fish genus Poeciliopsis (Atheriniformes: Poeciliidae).

Abstract: Genetic diversity in mtDNA was assd within the unisexual (all female) hybridogenetic fish Poecdiopsis monacha-occidentalis and the two sexual species from which it arose. Results confirm that P. monacha was the maternal ancestor and that paternal leakage of P. occidentals mtDNA has not occurred. Of particular interest is the high level of de novo mutational divergence within one hybridogenetic lineage that on the basis of independent zoogeographic considerations, protein electrophoretic data, and tissue gaftng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 21 publications
6
60
0
Order By: Relevance
“…The parthenogenetic grasshopper Warramaba virgo was estimated to be ca 300 000 years old (Kearney et al 2006). In unisexual fishes (Poeciliopsis complex), mtDNA variability was high indicating a rather ancient origin (Quattro et al 1992). Similar results were found in parthenogenetic geckos (Moritz & Heideman 1993;Kearney et al 2006).…”
Section: Interspecific Hybridization Leading To the Origin Of The Amasupporting
confidence: 74%
See 1 more Smart Citation
“…The parthenogenetic grasshopper Warramaba virgo was estimated to be ca 300 000 years old (Kearney et al 2006). In unisexual fishes (Poeciliopsis complex), mtDNA variability was high indicating a rather ancient origin (Quattro et al 1992). Similar results were found in parthenogenetic geckos (Moritz & Heideman 1993;Kearney et al 2006).…”
Section: Interspecific Hybridization Leading To the Origin Of The Amasupporting
confidence: 74%
“…They are often assessed as evolutionary 'dead ends' (Bell 1982). Many species, however, are rather abundant, show large ranges of geographical distribution and have shown to be evolutionary older than predicted from theoretical models (Quattro et al 1992;Schartl et al 1995b;Kearney et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Poeciliopsis divided about 8-16 million years ago (Mateos & Vrijenhoek 2002). The hybridogen, Poeciliopsis monacha-occidentalis based on mitochondrial evidence may be 150,000 years old (Quattro et al 1992) and lives throughout Sonora, Mexico and mates with males of the sexual species P. occidentalis. A similar history may hold for Amazon mollies.…”
Section: Discussionmentioning
confidence: 99%